Developing the Wonderful Digital Machine (WDM) Android Application for Local Wisdom-Based Islamic Learning in Banten - Mohamad Maulidin Alif Utama; Dahari Dahari; Wafa'un Lathifah (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
This study aimed to develop the Wonderful Digital Machine (WDM) Android application as a local-wisdom-based Islamic learning medium for students at Islamic Higher Education Institutions (PTKI) in Banten Province. It was motivated by the limited relevance of conventional learning media to the characteristics of digital-native learners. The study employed a Research and Development (R&D) approach based on the Hannafin and Peck model, which comprises needs analysis, design, development, and implementation stages. Data were collected through observations, interviews, questionnaires, and tests, and analyzed qualitatively and quantitatively, with validity, reliability, practicality, and effectiveness assessed. The findings indicate that the WDM application is highly feasible, as shown by strong validation scores from subject-matter, language, and media experts. The effectiveness test involving 86 students showed a significant improvement in learning outcomes, with the mean pretest score increasing from 63.02 to 91.86 on the posttest. Wilcoxon analysis yielded Z = −8.113, p < .001, confirming a statistically significant difference after implementation. This study also proposes the Local Wisdom-Based Digital Learning Media Model (MPDKL), which emphasizes the integration of local wisdom, online and offline flexibility, interactive features aligned with digital-native characteristics, and contextual transformation of religious behavior. Thus, the WDM application is effective in improving students’ learning outcomes while strengthening local wisdom values in Islamic higher education within a culturally relevant and technologically responsive learning environment for PTKI students.